2020
DOI: 10.2196/19433
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Mobile App (iGAM) to Promote Gingival Health by Professional Monitoring of Dental Selfies: User-Centered Design Approach

Abstract: Background Dental visits are unpleasant; sometimes, patients only seek treatment when they are in intolerable pain. Recently, the novel coronavirus (COVID-19) pandemic has highlighted the need for remote communication when patients and dentists cannot meet in person. Gingivitis is very common and characterized by red, swollen, bleeding gums. Gingivitis heals within 10 days of professional care and with daily, thorough oral hygiene practices. If left untreated, however, its progress may lead to teet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 34 publications
1
21
0
1
Order By: Relevance
“…Recently, we presented iGAM [21] which is the first mHealth app for monitoring gingivitis using dental selfies. In a qualitative pilot study, we showed the potential acceptance of iGAM to facilitate information flow between dentists and patients, which may be especially useful when face-to-face consultations are not possible.…”
Section: Dental Scientific Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we presented iGAM [21] which is the first mHealth app for monitoring gingivitis using dental selfies. In a qualitative pilot study, we showed the potential acceptance of iGAM to facilitate information flow between dentists and patients, which may be especially useful when face-to-face consultations are not possible.…”
Section: Dental Scientific Backgroundmentioning
confidence: 99%
“…The participants were using the application developed by us, the iGAM app which is currently available on the Google Play store (https://play.google.com/store/ apps/details?id=com.igmpd.igam). The application development process was described in a recently published article [21]. Following initial registration, the patient logs in, personal patient data (such as age, gender, etc.)…”
Section: Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…The SCRUM development methodology proved to be efficient, enabling the division of the project into small increments; this methodology allowed for tests, rapid changes when necessary, and weekly deliveries to the end user. Functional software deliveries in a shorter period (1 week) generated greater customer satisfaction and provided a development environment with motivated individuals, as reported by Tobias and Spanier [ 37 ].…”
Section: Discussionmentioning
confidence: 93%
“…Dental medicine is so depended on photography now that a good dental treatment cannot be conceived by an X-Ray photograph. There are many studies emphasizing the role of photography in detecting and following up dental and oral cavity pathology (Sofyanti et al, 2020, Dave et al, 2020, Costa et al, 2020, Tobias & Spanier, 2020, Konishi et al, 2020.…”
Section: Application Of Photography In Sciencesmentioning
confidence: 99%